Pleural decortication and hyperthermic intrathoracic chemotherapy for pseudomyxoma - Viktor Proesmans; Tom Vandaele; Jan Van Slambrouck; Albert Wolthuis; André D´Hoore; Jeroen Dekervel; Eric Van Cutsem; Raphaëla Dresen; Gert De Hertogh; Karlien Degezelle; Dirk Van Raemdonck; Philippe Nafteux; et al. (International Journal of Hyperthermia)
Aim: Pleural dissemination of pseudomyxoma peritonei (PMP) is an extremely rare diagnosis, for which no standard therapy is available.Methods: We describe the successful treatment of a 67-year-old male diagnosed with left-sided intrapleural dissemination of PMP (low-grade appendiceal mucinous neoplasm), 2 years after treatment of abdominal PMP with cytoreductive surgery (CRS) and hyperthermic intra-peritoneal chemotherapy. Treatment consisted of extended pleural decortication (ePD) and oxaliplatin-based hyperthermic intrathoracic chemotherapy (HITHOC). The patient is doing well without complications or signs of recurrence, 26 months after thoracic surgery.Conclusion: ePD in combination with HITHOC is a valuable treatment for thoracic PMP.